Measuring the international business sector and its two-decade dynamics in OECD countries - Sergii Arkhiiereiev; Anastasiia Mytrofanova (Cogent Economics & Finance, 2022)
The aim of this study is to assess the contribution of the international business sector (IBS) to the development of the national economy. A new index has been developed, which is expressed as a primary income share and makes it possible to analyze IBS structure both by the primary income from abroad (received) share and by the value added export share. This study analyzes the long-term development trends of IBS and its structural shifts for OECD and top non-OECD countries. Our new index has increased markedly in OECD countries, where IBS generated a third of primary income in the middle of the second decade of the analyzed period. In contrast, in top non-OECD member countries, this index grew slowly, while IBS generated about one-fifth of primary income. To analyze qualitative shifts in IBS growth in terms of cluster analysis OECD countries have been grouped according to the prevailing IBS models. The results showed that OECD countries changed their basic IBS model moving from the Partial model to the Dual one. It is the change in this basic model that accounts for the long-term trend of increasing gap in the development level of IBS in OECD and top non-OECD countries.
Keywords: F20; F40; F60; O11; O15; 330; International business sector; value added export to GDP ratio; primary incomeshare; OECD countries